Strategi Pengembangan Sektor Unggulan dalam Pembangunan Ekonomi Berkelanjutan Kabupaten Lamongan: (STRATEGI PENGEMBANGAN SEKTOR UNGGULAN DALAM PEMBANGUNAN EKONOMI BERKELANJUTAN KABUPATEN LAMONGAN) - Mutmainah, Imroatul; Cahyono, Hendry (Independent: Journal of Economics, 2021)
The purpose of this research is to determine the leading sectors of Lamongan Regency by using Location Quotient and Shift Share analysis. The data used in this research is the Gross Regional Domestic Product (PDRB) of Lamongan and East Java Regency for 10 years, 2010-2019. The method used is a mixed method, namely quantitative descriptive and literature study. The results showed that the sector based on LQ> 1 is the agricultural sector; construction; transportation and communication; and the services sector. Meanwhile, the non-base sector is the mining and quarrying sector; processing industry; electricity, clean water and gas; real estate sector, corporate services sector; and the financial sector with LQ <1. The result of the shift share value in all sectors of Lamongan Regency with a positive value means that regional growth is experiencing rapid growth. The analysis of the sustainable development economic strategy uses a literature study where Lamongan Regency has not yet reached sustainable development if it is only seen from the economic aspect and does not see all aspects in the sustainable development component. Different policy strategies are needed so that in each aspect in the Lamongan Regency area in an effort to accelerate achievements towards the sustainable development of Lamongan Regency. Keywords: Economic Development, Leading Sectors, Sustainable Development, Lamongan Regency